Gardenia merdeka edition - Mohd Samahani, Wan Muhammad Lutfi (Universiti Teknologi MARA, Perak, 2022)
Gardenia Merdeka edition is a project that focusing on the effectiveness of graffiti art. This project is to bring more freshers and youthful towards Gardenia Quick Bites’ products – Quick Bites Corn Cream Roll, Quick Bites Vanilla Cream Roll, and Quick Bite Chocolate Cream Roll, by using graffiti art as a medium and traditional dance as the elements.